PELATIHAN PEMILIHAN MEDIA PEMBELAJARAN BAGI GURU SMPIT INSAN MULIA ABUNG SEMULI LAMPUNG UTARA - Venty Meilasari; Fhela Vhantoria Ningrum (Universitas Sarjanawiyata Tamansiswa, 2022)
Google Classroom and whatsapp are the places used in the distance learning process. The use of Google Classroom and whatsapp as a learning medium is often without considering the student's perspective. The efficiency of learning media in making it easier for students to learn. Basically, in choosing learning media, it must be by systematic and planned procedures. The purpose of this community service activity is to increase knowledge regarding the procedure for selecting learning media. The target of the service is a teacher at SMPIT Mulia Abung Semuli, North Lampung. The activity was carried out on November 28, 2021, for 9 hours of lessons. The stages of activity were preparation, socialization, and training. Preparation stage activities related to determining Partners, preliminary studies, formulation of activities, and coordination with partners. The socialization stage is related to the delivery of learning media selection procedure materials, studying learning objectives and teaching materials, and demonstrating how to use video tutorial media using a pen tablet, Cabri 3D application-assisted media, and the use of mobile learning using Smart Apps Creator. The training stage is related to making video tutorials using a pen tablet, media assisted by the Cabri 3D application, and the use of mobile learning using Smart Apps Creator by teachers, and reviewing the ability to learn media. The result of the activity is an increase in knowledge about the procedure for selecting learning media, namely studying learning objectives, studying teaching materials, user abilities, and reviewing learning media abilities